# Thread: Making a pronumeral the subject

1. ## Making a pronumeral the subject

Can someone please solve Rp=R1 R2/R1+R2 to make R the subject!

And for a bunus C=N-n/2p to make p the subject.

Thanks so much!!

2. Originally Posted by JKDste
Can someone please solve Rp=R1 R2/R1+R2 to make R the subject!

And for a bunus C=N-n/2p to make p the subject.

Thanks so much!!
Please either use brackets in the correct places, or use LaTeX.

Is the first one

$R_p = \frac{R_1R_2}{R_1 + R_2}$?

Is the second

$C = \frac{N - n}{2p}$?

3. Yeah thats it! Sorry I didn't know how to type it out like that!

Thanks so much!

4. Your first question doesn't make sense, since you don't have $R$ as a variable.

Are you trying to make $R_1$ or $R_2$ the subject?

Q.2) $C = \frac{N - n}{2p}$

$2Cp = N - n$

$p = \frac{N - n}{2C}$.

5. Originally Posted by Prove It
Your first question doesn't make sense, since you don't have $R$ as a variable.

Are you trying to make $R_1$ or $R_2$ the subject?

Q.2) $C = \frac{N - n}{2p}$

$2Cp = N - n$

$p = \frac{N - n}{2C}$.

Thanks Prove it, the subject for the other one was R1

6. $R_p = \frac{R_1R_2}{R_1 + R_2}$

$R_p(R_1 + R_2) = R_1R_2$

$R_1R_p + R_2R_p = R_1R_2$

$R_1R_p - R_1R_2 = -R_2R_p$

$R_1(R_p - R_2) = -R_2R_p$

$R_1 = -\frac{R_2R_p}{R_p - R_2}$

$R_1 = \frac{R_2R_p}{R_2 - R_p}$.